Locallah / Muhammad Faliq Aizat M.Amran ... [et al.] - M.Amran, Muhammad Faliq Aizat; Istekhar Ahmad, Nazmeen Fatima; Alias, Nur Izzati Nabilah; Mohamad Faizal, Adriana; Mohd Hardy, Mohd Arsy Ardy (2021)
According to Datuk Seri Nancy Shukri, Minister of Tourism, Arts and Culture Malaysia (2021), the sales of Malaysia handicraft products have decreased from RM519 million in 2019 to RM200 million in 2020. Furthermore, Pasar Seni had a lesser visitor every day and hit the lowest due to the COVID-19 pandemic (Bernama, 2021). This has caused economic and social disruption to the handicraft business owners. To counter this issue, we innovated an application called Locallah. It is an application related to the tourism industry which acts as intermediaries between handicraft business owners and customers. The objectives of Locallah are 1) to help handicraft business owners in promoting their products, 2) to increase profit by eliminating excessive intermediaries' cost, and 3) to educate local entrepreneurs and the users. The novelties of Locallah are to promote handicraft products from rural areas, to facilitate handicrafts business owner in sustainable business, and to educate in the importance of selling and buying from local handicrafts market. This application brings an impact on 1) the economy as it helps handicraft business owners to gain more profit and helps in job creation, and 2) the social as it educates the seller and buyer on importance in local handicrafts market. Lastly, the potential of commercialization can be seen in the ease of use of the application. In addition, the Malaysian Communication and Multimedia Commission (MCMC) (2018) stated that there are 26.7 million Malaysian use smartphones and 15.3 million people use the internet for online purchase and booking. This number indicates the significance of using smartphones and applications to which the travel and tourism industry is proceeding.